Generation Z Consumer Satisfaction in Online Shopping - Utami, Rahayu Tri; Dewanti, Yopy Ratna; Darmawan, Darmawan (Journal Socio Humanities Review, 2021)
Generation Z is the generation born from 1998 – 2010. Similar to Millennials, Generation Z likes to shop at offline stores as a social activity. But this generation is also one of the generations who use their smartphones the most to find the product they want to buy. The characteristics of the millennial and z generations that are closely related to technology are then used by e-commerce companies for promotion. It is proven that almost all sources of information about e-commerce come from digital media.Conducted a series of tests on hypotheses using predetermined statistical analysis techniques, namely correlation analysis, both simple and multiple regression with a total of 140 respondents who filled out the questionnaire. The influence between the variable price (X1) and consumer satisfaction Generation Z (Y) of rxy = 0.147 is very low. The influence between the Promotion variable (X2) and Generation Z (Y) consumer satisfaction of rxy = 0.138 is very low. The relationship between the variable Price (X1) and Promotion (X2) of rxy = 0.999 is classified as very high (strong). The simultaneous influence of Price (X1) and Promotion (X2) variables on Generation Z (Y) consumer satisfaction of 0.218 is relatively low. Generation Z consumer satisfaction in online shopping through selling prices and promotions can increase sales results and consumer satisfaction.